Is financial globalization truly global? New institutions for an inclusive capital market - Philip Arestis; Santonu Basu (Levy Economics Institute of Bard College, 2003)
In 2002 more than 1 trillion worth of new bonds was sold across international boundaries. The total stock of cross-border bond holdings was more than 9 trillion. Such lending, together with sales of equities, is regarded as one of the chief benefits of globalization. But financial investment does not always flow where it is needed most. While it appears that the world cannot be satiated with US securities, issues of emerging economies account for less than 6 percent of total international holdings of debt securities (D'Arista 2003). And, as Argentina discovered recently, international lenders can be fickle, selling enough foreign currency and securities to cause a currency crisis.
Keywords: 330; Finanzmarkt; Globalisierung; Kapitalmarktliberalisierung; Kapitalmobilität; Welt